Novel Expression of Vascular Endothelial Growth Factor Receptor (VEGFR)-3 and VEGF-C on Corneal Dendritic Cells - Hamrah, Pedram (American Society for Investigative Pathology, 2003)
Vascular endothelial growth factor-3 (VEGFR-3) plays a critical role in embryonic cardiovascular development and is thought to be expressed exclusively on the lymphatic endothelium, high endothelial venules, and rarely on adult vascular endothelium. Recent evidence also suggests expression of VEGFR-3 on some tumor-associated macrophages. We have studied the expression of VEGFR-3, its ligand VEGF-C and the co-receptor neuropilin-2, in normal and inflamed corneas and characterized the phenotype and distribution of VEGFR-3(+) cells. Our data demonstrate, for the first time, the expression of VEGFR-3 on corneal dendritic cells (DC) and its up-regulation in inflammation. VEGFR-3(+) DC are CD11c(+)CD45(+)CD11b(+), and are mostly major histocompatibility (MHC) class II(−)CD80(−)CD86(−), indicating immature DC of a monocytic lineage. During inflammation, there is rapid increase in the number of VEGFR-3(+) DC in the cornea associated with heightened membranous expression as compared to a mostly intracellular expression in uninflamed tissue. VEGFR-3(+) DC in normal corneas are VEGF-C(−)neuropilin-2(−), but express VEGF-C in inflammation. Interestingly, similar cells are absent both in the normal and inflamed skin. These data demonstrate, for the first time, the expression of VEGFR-3 and VEGF-C on tissue DC, which implicate a novel potential relationship between lymphangiogenesis and leukocyte trafficking in the eye.